Juvenile Conflict: The War Among K-POP Idol Fans on Twitter - Miftahana Alfira Izzati; Elisa Fitrotul Mutoharoh; Isnaini Nur Adibah; Asfarina Wiegya Qaulan Syadida; Ihya Ulumuddin (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2023)
The target of this hypothesis is to exhibit that the Korean Wave, also known as Korean Hallyu, currently controls the entertainment industry. Similarly, what transpired in Indonesia? Publications claim that Indonesia has the highest population of K-POP followers worldwide. Based on a survey's got the latest by Kumparan.com and IDN Times, it was stated that 57% and 47.4% of K-POP fans were teenagers. This proves that the big chunk of K-POP enthusiasts in Indonesia are millennials. Teen fans who are known to be unable to control their emotions and have less self-control will be easily provoked when they see differences of opinion regarding their idol. This will give rise to verbal wars between K-POP fans or Fan wars. Gaining knowledge about fan conflicts among young K-POP fans and its effects is the main goal of this study. A literature research was used as the methodology. The study's data showed that the fan war's effects on millennials have both positive and bad aspects. Where the existing impact certainly influences the daily life of these idol fans. Keywords : Juvenile Conflict, Fan war, K-POP, Social Media.